Heling en heil is nie moontlik sonder waarheid nie - Thesnaar, CH (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
Healing and salvation is not possible without truth This research continues to contribute to healing and reconciliation in a post-Truth and Reconciliation Commission context within South-Africa, by focusing on truth as a key aspect in the healing and reconciliation process. In this regard Archbishop emeritus Desmond Tutu makes a significant point when he states “There can be no healing without truth. The Truth and Reconciliation Commission helped us to also understand truth as healing and restorative truth. This seems to support the movement towards a more relational, personal, subjective and narrative understanding of truth. The church can contribute to the process of healing and reconciliation by creating safe spaces where healing as transformative truth can help people deal with the past. This contribution wants to reconfirm the importance of the meaning of truth for healing and reconciliation in a time where truth is under pressure.